Use of Lavage Fluids in Arthroplasty to Prevent Postoperative Infections - Kruckenhauser, E.-M.; Nogler, M.; Coraça-Huber, D. (Drug Research, 2014)
Lavage techniques are used every day all over the world to clean wounds and surgical approaches. The solutions used vary depending on the application range; there are, for instance, normal saline, antibiotic or antiseptic solutions. This review describes the lavage solutions actually used during arthroplasty and their outcome related to postoperative infections.This is a retrospective review of published articles and books. The information was obtained from online browsers for scientific articles.The lavage fluids used in arthroscopy and those used in experimental studies were normal saline, bacitracin, castile soap, benzalkonium chloride, povidone iodine, Ringer’s solution, neomycin sulphate, ethanol, chlorhexidine gluconate, cephalothin sodium, and carbenicillin indanyl sodium.As few clinical studies were carried out with lavage solutions, most of the results are based on experimental studies. A “golden standard” is still missing.
Keywords: antibacterial drugs; infectious diseases; skin pharmacology